# Literal Equations.Solve for x:3x-a/b = 3x-b/a

2
by franceslowisa

2014-05-13T20:41:14+08:00

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(3x-a)/b = (3x-b)/a

Multiply the equation by ab:
a (3x-a) = b (3x-b)

3ax - a
² = 3bx - b²

Isolate terms with x:
3ax -3bx = a² -b²

Factor out similar factors:
3x(a-b) = a² - b²

Divide both sides by 3(a-b):
x = (a² -b²) / 3(a-b)

Note that a² -b² = (a+b) (a-b):
x = (a+b) / 3
2014-05-14T19:45:43+08:00

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
3x-a/b =3x-b/a
multiply b to 3x and on the other side also multiply a to 3x:
so we get:
3bx-a=3ax-b
the we will transpose 3ax to the left and -a to the other side
so we get:
3bx-3ax=a-b
then factor out 3x:
3x(b-a)=a-b
so x= a-b/3(b-a)
then change the sign of 3 into negative to cancel out a-b
it becomes:
x=a-b/-3(a-b)
so x=-1/3